The Effect of Tax Rates and Tax Payment Mechanisms on The Compliance of MSME Taxpayers in Pemogan Village, South Denpasar District - Minceana Pau; Luh Diah Citraresmi Cahyadi; Rai Gina Artaningrum (LPPM Universitas Dhyana Pura, 2026)
This investigation explored the compliance of MSME taxpayers in Pemogan Village, South Denpasar District, by looking at the effects of tax rates and payment procedures. A total of 48 MSME operators participated, representing the entire local MSME population. Data were gathered using a questionnaire based on a Likert scale and the data were evaluated with Multiple Linear Regression. Participants were chosen through random sampling, ensuring everyone had an equal chance of selection. The findings suggest that both the way taxes are calculated and the payment mechanisms contribute positively to enhancing MSME compliance in the village.